Educational Status of Scheduled Tribes in Erstwhile State of Jammu and Kashmir Contesting the idea of Inclusion - Jahangir, Mohmad Saleem; Shumaila; Wani, Nadeem Ahmad (JOURNAL OF INDIAN EDUCATION, 2021)
The role of education is crucial in progress towards creating more inclusive and just societies. It is the most effective tool for overcoming the exclusion of economically and socially marginalised sections of the society. The Scheduled Tribes represent one of the marginalised sections of the society lagging behind in most of the human development indicators especially literacy. The paper argues that despite constitutional guarantees and other related efforts, the Scheduled Tribes of Jammu and Kashmir continue to lag behind in education as compared to the mainstream population. The paper aims to investigate the educational status of Scheduled Tribes in Jammu and Kashmir by highlighting the trend of their literacy rate, gross enrolment ratio and dropout rate. Tribal education is a matter of great concern in Jammu and Kashmir, which necessitates the removal of disparities and equalisation in educational opportunities by addressing the special needs of those who have been deprived so far.